2017
DOI: 10.2174/1871530317666170320113613
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Neuroendocrine Dysregulation in Patients with Osteoarthritis: A Revision and a Pilot Study

Abstract: An immune-neuroendocrine dysregulation affecting both systemic inflammatory and stress mediators and the function of innate immune cells underlies OA. This reflects an altered feedback between the innate/inflammatory and stress responses in this pathology.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 0 publications
2
22
0
1
Order By: Relevance
“…Besides, researchers also found that immune complexes and immunoglobulins against cartilage components were detected in the synovium, plasma, and cartilage of patients with OA (Qian et al, ). Further studies confirmed that immune‐neuroendocrine dysregulation in OA could affect systemic inflammatory, stress mediators, and the function of innate immune cells, making it meaningful to investigate the pathophysiological mechanisms of immune response and inflammatory response in the development of OA (Gálvez et al, ). Apoptosis and inflammation of chondrocytes are one of the most important mechanisms in the pathogenesis of OA.…”
Section: Discussionmentioning
confidence: 98%
“…Besides, researchers also found that immune complexes and immunoglobulins against cartilage components were detected in the synovium, plasma, and cartilage of patients with OA (Qian et al, ). Further studies confirmed that immune‐neuroendocrine dysregulation in OA could affect systemic inflammatory, stress mediators, and the function of innate immune cells, making it meaningful to investigate the pathophysiological mechanisms of immune response and inflammatory response in the development of OA (Gálvez et al, ). Apoptosis and inflammation of chondrocytes are one of the most important mechanisms in the pathogenesis of OA.…”
Section: Discussionmentioning
confidence: 98%
“…The neutrophils' phagocytic capacity against opsonized bacteria (Staphylococcus epidermidis) was evaluated by flow cytometry of heparinized whole blood. This quantitative technique allows the evaluation of the percentage of active 'phagocytic neutrophils' and the number of bacteria ingested per cell by measuring the mean fluorescence intensity (MFI) of active phagocytic cells, which reflects the phagocytic activity of neutrophils [8]. In brief, bacteria were stained with fluorescein isothiocyanate (FITC) (1 lg/ml) and opsonized with human serum.…”
Section: Study Of the Neutrophils' Phagocytic Capacitymentioning
confidence: 99%
“…In addition to local inflammatory events occurring within joint tissues such as the release of inflammatory mediators by cartilage, bone and synovium [4,5], low-grade systemic inflammation also plays a pivotal role in this condition. The presence of low-grade systemic inflammation could lead to the initiation and aggravation of OA, whereas locally produced inflammatory mediators, such as cytokines, might be reflected in peripheral blood and contribute to perpetuate this systemic inflammatory status [6][7][8]. Patients with OA also present changes in peripheral blood T cell composition [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations